Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006344.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous healthcare worker involvement for Indigenous adults and children with asthma

Abstract: The involvement of IHW in asthma programs targeted for their own ethnic group in one small trial was beneficial for some but not all asthma outcomes. Thus there is insufficient data to be confident that the involvement of IHW is beneficial in all settings. Nevertheless, given the complexity of health outcomes and culture as well as the importance of self-determination for indigenous peoples, the practice of including IHW in asthma education programs for indigenous children and adults with asthma is justified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“… 5 of 9 studies found statistical improvements in asthma symptoms compared to control. Chang 2010 [ 29 ]** 1 RCT 113 participants R-AMSTAR 40 RCT 2010 Education by IHWs vs. education no IHW. FU: 12 mo Impact: Target: Ethnic groups Initial clinical consultation, reinforced by home visits from a trained IHW.…”
Section: Methodsmentioning
confidence: 99%
“… 5 of 9 studies found statistical improvements in asthma symptoms compared to control. Chang 2010 [ 29 ]** 1 RCT 113 participants R-AMSTAR 40 RCT 2010 Education by IHWs vs. education no IHW. FU: 12 mo Impact: Target: Ethnic groups Initial clinical consultation, reinforced by home visits from a trained IHW.…”
Section: Methodsmentioning
confidence: 99%
“…This was created by hand searching a selected set of journals. Informed by two published search strategies 19,20 , authors Sladek and Tyndall constructed a search strategy for Australian Indigenous health, limiting results to a publication year of 2006 ( Table 1). Citations were downloaded into an End-Note file and ordered by journal title.…”
Section: Methodsmentioning
confidence: 99%
“…By expanding the patients' access to a language concordant physician, the risk of a misperception of the patients' symptom will be reduced. [ 25 26 27 30 31 ] Our findings suggest that Swedish speaking emergency patients' less frequent healthcare visits could relate to discordant communication difficulties. The bilingual Swedish speakers might not have words in Finnish for expressing health problems and consequently avoid complicated discussions.…”
Section: Discussionmentioning
confidence: 87%